Contralateral lymph node metastasis: A rare skip pattern (Indian Journal of Case Reports, 2024)
Neck lymph node metastasis is the most critical factor influencing the survival and prognosis of oral squamous cell carcinoma. The outcome of patients with lymph node metastases occurring after excision or radiotherapy of the primary tumor is poor. In the absence of ipsilateral nodal metastases, contralateral lymph neck metastasis is extremely rare. Reports of skip metastases have been recorded for lesions of the tongue and floor of the mouth as there is free communication between the two sides of the tongue. Intraoperative frozen sections of neck nodes have been used as a modality for the detection of occult metastases and to guide the extent of neck dissection but have not provided satisfactory results. The case described in this report is a rare phenomenon that demonstrates a well-lateralized clinically advanced buccal mucosa carcinoma with histologically proven node-negative neck but exhibited contralateral positive neck after a span of 1 month.